Pengaruh OPEC (Organization of the Petroleum Exporting Countries) Terhadap Harga Bahan Bakar Minyak di Indonesia - Muhamad Gani Fansyah; Bayu Firmansyah; Yulisa Tri Hapsari; Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
OPEC (Organization of the Petroleum Exporting Countries) plays a critical role in regulating the global supply of crude oil through its production policies. The organization's decisions, such as increasing or reducing oil production quotas, directly impact global crude oil prices, influencing various economic aspects, including domestic fuel prices in Indonesia. As an oil-importing country, Indonesia is significantly affected by fluctuations in global oil prices, which are influenced by OPEC's policies. These fluctuations impact the purchasing power of society, production costs in industries, and inflation. This study analyzes the relationship between OPEC's production policies, global crude oil price fluctuations, and their effects on domestic fuel prices in Indonesia. The research employs a qualitative descriptive method using secondary data from OPEC and Pertamina, focusing on trends in oil production and pricing. The findings highlight the interconnectedness between OPEC's production strategies and Indonesia's energy sector, offering valuable insights for policymakers to adaptively address energy stability and ensure national energy resilience